Prenatal acute thermophysiological stress and spontaneous preterm birth in Western Australia, 2000–2015: A space-time-stratified case-crossover analysis - Nyadanu, Sylvester; Tessema, Gizachew; Mullins, Ben; Pereira, Gavin (ELSEVIER GMBH, 2022)
Epidemiologic evidence on acute heat and cold stress and preterm birth (PTB) is inconsistent and based on ambient temperature rather than a thermophysiological index. The aim of this study was to use a spatiotemporal thermophysiological index (Universal Thermal Climate Index, UTCI) to investigate prenatal acute heat and cold stress exposures and spontaneous PTB. We conducted a space-time-stratified case-crossover analysis of 15,576 singleton live births with spontaneous PTB between January 1, 2000 and December 31, 2015 in Western Australia. The association between UTCI and spontaneous PTB was examined with distributed lag nonlinear models and conditional quasi-Poisson regression. Relative to the median UTCI, there was negligible evidence for associations at the lower range of exposures (1st to 25th percentiles). We found positive associations in the 95th and 99th percentiles, which increased with increasing days of heat stress in the first week of delivery. The relative risk (RR) and 95% confidence interval (CI) for the immediate (delivery day) and cumulative short-term (up to six preceding days) exposures to heat stress (99th percentile, 31.2 °C) relative to no thermal stress (median UTCI, 13.8 °C) were 1.01 (95% CI: 1.01, 1.02) and 1.05 (95% CI: 1.04, 1.06), respectively. Elevated effect estimates for heat stress were observed for the transition season, the year 2005–2009, male infants, women who smoked, unmarried, ≤ 19 years old, non-Caucasians, and high socioeconomic status. Effect estimates for cold stress (1st percentile, 0.7 °C) were highest in the transition season, during 2005–2009, and for married, non-Caucasian, and high socioeconomic status women. Acute heat stress was associated with an elevated risk of spontaneous PTB with sociodemographic vulnerability. Cold stress was associated with risk in a few vulnerable subgroups. Awareness and mitigation strategies such as hydration, reducing outdoor activities, affordable heating and cooling systems, and climate change governance may be beneficial. Further studies with the UTCI are required.